Answer :


= - 3x3y3bx + x2y4bx


= -3x4y3b + x3y4b


According to question:


When x = 1 and y = 2


= - 3 (1)4 (2)3 b + (1)3 (2)4 b


= - 3 (8) b + 3 (8) b


= 0


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Fill in the blankNCERT - Mathematics Exemplar

Multiply the monoRD Sharma - Mathematics

Find the followinRD Sharma - Mathematics

Find the followinRD Sharma - Mathematics

Find the followinRD Sharma - Mathematics

Find the followinRD Sharma - Mathematics

Find the followinRD Sharma - Mathematics

Find the followinRD Sharma - Mathematics